Association of Dialysis Malnutrition Score with Hypoglycemia and Quality of Life among Patients with Diabetes on Maintenance hemodialysis - Uy, Melissa Claire (J ASEAN Fed Endocr Soc, 2018)
OBJECTIVE: To determine the association between Dialysis Malnutrition Score (DMS), hypoglycemia and quality of life among patients with Diabetes on Maintenance Hemodialysis (MHD). METHODOLOGY: Ninety-two diabetic patients on maintenance hemodialysis were assessed using a standardized data collection tool, Dialysis Malnutrition Score, WHOQoL-BREF questionnaire, anthropometric measurements and hourly blood sugar monitoring during the dialysis session. Association among DMS, hypoglycemia and quality of life were assessed along with other associated variables. RESULTS: Based on the DMS, 62% of patients were malnourished. Those with malnutrition were significantly older (p=0.0006) and female (p=0.013). Only 6.5% of the participants developed hypoglycemia during dialysis. Those with poor nourishment in the DMS showed a significant trend of decrease in the quality of life (physical (p<0.001), psychological (p<0.001) and social (p=0.004) and is associated with the occurrence of hypoglycemia (p<0.001). CONCLUSION: Malnutrition is prevalent in diabetic patients on MHD using DMS. A higher DMS score is highly correlated with increased risk of hypoglycemia and decreased quality of life hence detection of malnutrition is important to prevent further nutritional depletion, hypoglycemia and poor patient outcomes by implementing preventive measures such as nutritional counselling and psychosocial interventions.